A method for constructing a basalt fiber concrete damage model under sulfate erosion

By constructing a concrete damage model coupled with sulfate attack and basalt fiber content, the limitations of single-factor analysis in existing technologies are overcome, enabling comprehensive characterization and accurate assessment of concrete damage and enhancing its guidance for engineering applications.

CN122631425APending Publication Date: 2026-08-25HOHAI UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610765259.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing technologies fail to effectively combine the coupled analysis of sulfate attack and basalt fiber content, and the test conditions do not match actual engineering. They only test compressive/tensile strength and lack stiffness indicators such as elastic modulus, thus failing to comprehensively characterize the damage.

Method used

A concrete damage model based on Lemaitre's equivalent strain theory, coupling sulfate attack with basalt fiber content, was constructed. Concrete specimens were prepared by soaking them in sulfate solutions of different concentrations, and the elastic modulus and tensile strength were tested to establish the coupling relationship of damage variables and optimize the model parameters to match the experimental results.

Benefits of technology

It enables precise quantification of the synergistic effects of fiber content and sulfate concentration on concrete damage under sulfate attack conditions, providing a comprehensive damage description and enhancing the guiding value and accuracy of the model for engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122631425A_ABST
    Figure CN122631425A_ABST
Patent Text Reader

Abstract

The application discloses a basalt fiber concrete damage model construction method under sulfate erosion, and is based on C30 basalt fiber concrete mechanical property test data and Lemaitre equivalent strain theory, constructs a basalt fiber concrete damage model under sulfate erosion, reasonably evaluates the comprehensive influence of sulfate erosion concentration and basalt fiber mixing amount on the mechanical property change of C30 basalt fiber concrete, so as to accurately control the fiber mixing amount when basalt fiber concrete is used in the engineering construction environment with high sulfate content, and to improve the erosion resistance and durability of facilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete mechanics and durability technology, specifically relating to a method for constructing a damage model of basalt fiber reinforced concrete under sulfate erosion. Background Technology

[0002] In sulfate-rich natural environments (such as saline-alkali land, coastal areas, and high-salt water conservancy projects), concrete structures are susceptible to sulfate erosion: sulfate ions react chemically with concrete hydration products to produce expansive substances, leading to increased internal porosity, decreased stiffness, and deterioration of mechanical properties, severely shortening the service life of the project.

[0003] Incorporating fibers into concrete has become a major method in recent years to improve the tensile and compressive strength and toughness of concrete, thereby enhancing its resistance to sulfate attack. Basalt fibers possess characteristics such as high elastic modulus, good tensile strength, and strong corrosion resistance. When added to concrete in appropriate amounts, they can fill pores, connect the matrix, and create a dense whole, playing a good bridging and stress transfer role, increasing tensile and compressive strength and toughness, and improving resistance to sulfate attack. However, there is an "optimal range" for fiber content—appropriate addition can fill pores and play a bridging role, while excessive addition will cause agglomeration and reduce the cohesiveness of the matrix.

[0004] Existing technologies have the following shortcomings: 1) Single factor: Most models only consider the effects of sulfate attack or fiber content alone, failing to achieve coupled analysis of the two. 2) Deviation from operating conditions: The tests often use "wet-dry cycle accelerated erosion," which does not match the long-term immersion conditions of concrete in actual engineering. 3) One-sided indicators: Only compressive / tensile strength is tested, lacking stiffness indicators such as elastic modulus, which cannot comprehensively characterize the damage. Therefore, there is an urgent need to construct a basalt fiber reinforced concrete damage model that fits actual operating conditions, covers the coupling of two factors, and has a solid theoretical foundation. Summary of the Invention

[0005] The purpose of this invention is to provide a method for constructing a damage model of basalt fiber reinforced concrete under sulfate erosion, thereby solving the aforementioned technical problems in the prior art.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:

[0007] A method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion includes the following steps:

[0008] Step S1: Prepare control group C30 plain concrete test blocks and experimental group C30 basalt fiber concrete test blocks, and immerse all test blocks in sulfate solutions of different concentrations for a preset time to erode them;

[0009] Step S2: Dry the concrete test blocks after soaking and erosion, and then conduct mechanical property tests to obtain at least two key mechanical property parameters;

[0010] Step S3: Analyze the variation law of the mechanical performance parameters, and construct a concrete damage model under the coupled effect of sulfate attack and basalt fiber content based on Lemaitre equivalent strain theory. The damage model includes the coupling relationship between sulfate attack damage variables and fiber content damage variables.

[0011] Step S4: Repeat the mechanical property test in step S2 to verify and correct the damage model so that the model fitting calculation results and the experimental test damage results meet the preset matching accuracy.

[0012] Further optimization was carried out. The raw materials for the control group test blocks included P·O42.5 cement, crushed stone with a particle size of 20~40mm, and natural river sand with a fineness modulus of 2.5. The raw materials for the experimental group test blocks included P·O42.5 cement, crushed stone with a particle size of 20~40mm, natural river sand with a fineness modulus of 2.5, and basalt fiber.

[0013] To further optimize, in step S1, the control group C30 plain concrete test block is designated as test block group A; the experimental group C30 basalt fiber concrete test blocks are divided into three groups, designated as test block group B, test block group C, and test block group D, respectively, with fiber volume contents of 0.5%, 1%, and 1.5% for the three groups of test blocks.

[0014] Each test block group contains multiple test blocks, and all test blocks are numbered, with each test block corresponding to a unique number. For each test block with a different number in each group, they are immersed in a solution with a sulfate concentration of 0%, 5%, 10%, 15%, and 20%, respectively, for a period of 30 days.

[0015] Further optimization involves conducting mechanical property tests on all test blocks in step S2, collecting the values ​​of the elastic modulus and tensile strength of different test blocks, and using the arithmetic mean of the values ​​measured by three parallel test blocks as a valid test result under the same influencing factors.

[0016] Further optimization, step S3 specifically includes:

[0017] Step S3.1: Define sulfate erosion damage variable D1: Using the elastic modulus E0 of the specimen corresponding to a sulfate concentration of 0% in specimen group A as the baseline value, and the elastic modulus E of the specimen corresponding to a sulfate concentration of n... n If the measured value is true, then: D1 = 1 - E n / E0;

[0018] If D1 < 0, it means that the mechanical properties of the concrete specimen are enhanced after soaking in sulfate solution;

[0019] D1=0 ​​indicates that the mechanical properties of the specimen were not damaged after soaking in sulfate solution;

[0020] If D1>0, it means that the mechanical properties of the test block have been damaged after soaking in sulfate solution.

[0021] Define the basalt fiber admixture effect variable D2: the tensile strength f of the specimen corresponding to a sulfate concentration of 0% in specimen group A. t0 Using the reference value, the tensile strength f of the specimen corresponding to a sulfate concentration of 0% in specimen groups B, C, or D is determined. tn If the measured value is true, then: D2 = 1 - f tn / f t0 ;

[0022] If D2 < 0, it means that the mechanical properties of the concrete specimen are enhanced after adding basalt fiber;

[0023] D2=0 indicates that the addition of basalt fiber has no effect on the mechanical properties of the concrete specimen;

[0024] If D2>0, it means that the mechanical properties of the concrete specimen have been damaged after the addition of basalt fiber.

[0025] Step S3.2: Establish the coupling relationship between D1 and D2:

[0026] Based on Lemaitre's equivalent strain theory, sulfate erosion damage and fiber doping damage are coupled to construct the total damage variable D. 12预 Constitutive relations:

[0027] ;

[0028] In the formula, D 12预 This represents the predicted values ​​of concrete damage variables under the coupling effect of sulfate attack and basalt fibers; when only sulfate attack exists, D2=0, D... 12预 =D1; When only the fiber content has an effect, D1=0, D 12预 =D2.

[0029] Step S3.3: Establish functional relationships:

[0030] The damage variable D1 is set to have a quadratic function relationship with the sulfate concentration: D1 = an² + bn + c, where n is the sulfate solution concentration and a, b, and c are coefficients to be determined.

[0031] The damage variable D2 is set to have a cubic function relationship with the basalt fiber content:

[0032] V f The volume content of basalt fiber, lf Indicates the length of basalt fibers, in mm; d f The diameter of the basalt fiber is expressed in μm. λ1 and λ2 represent the characteristic values ​​of basalt fibers, p is the adjustment parameter, and λ1 and λ2 represent the characteristic value coefficients of basalt fibers.

[0033] Step S3.4: Model parameter fitting: The sulfate is sodium sulfate. The functional relationship in step S3 is subjected to regression analysis using the test results of step S2 to obtain the fitting parameters.

[0034] The fitting parameters for D1 satisfy: a = 3.0 × 10 -4 b = -4.0 × 10 -4 c = -2.7 × 10 -3 ;

[0035] The fitting parameters for D2 satisfy: λ1 = 2.6265 × 10 -6 λ2=-3.2902×10 -9 p = 8.3784 × 10 -3 .

[0036] Further optimization involves obtaining two types of damage coupling models through parameter fitting in step S3.4:

[0037] The first type is a damage coupling model that considers the variation of basalt fiber volume content when the sulfate concentration is constant, as detailed below:

[0038]

[0039] Among them, D 12预 _0S、D 12预 _5S、D 12预 _10S、D 12预 _15S、D 12预 _20S represent the damage coupling models when the sulfate concentration is 0%, 5%, 10%, 15%, and 20%, respectively.

[0040] The first type is a damage coupling model that considers the variation of sulfate concentration with a fixed basalt fiber volume content.

[0041]

[0042] Among them, D 12预 _0F、D 12预 0.5F, D 12预 _1F、D 12预 _1.5F represents the damage coupling model when the volume content of basalt fiber is 0%, 0.5%, 1.0%, and 1.5%.

[0043] Further optimization, step S4 specifically includes:

[0044] Step S4.1: Determine the scope of the verification object: The test blocks corresponding to the 12 independent combinations of fiber volume content of 0.5%, 1%, and 1.5% and sulfate concentration of 5%, 10%, 15%, and 20% in the test groups are determined as verification test blocks. All verification test blocks constitute verification group E, and each combination contains no less than 3 parallel test blocks.

[0045] Step S4.2: Calculate the total measured damage for each combination in verification group E, specifically as follows:

[0046] 1) The elastic modulus E0 of the specimen in specimen group A with a sulfate concentration of 0% is used as the baseline value; the sulfate concentration n and basalt fiber volume content V in experimental group E are used as the baseline value. f The elastic modulus E of the corresponding test block n,vf If the measured value is given, then the damage D of the verification test block is... 1-( n,v f) =1-E n,vf / E0;

[0047] 2) The tensile strength f of the test block corresponding to a sulfate concentration of 0% in test block group A. t0 Using the sulfate concentration n and basalt fiber volume content V in experimental group E as the baseline values, f Corresponding elastic modulus f tn,vf If the measured value is given, then the damage D of the verification test block is... 2-( n,v f) =1-f tn,vf / f t0 ;

[0048] 3) The measured E n,vf f tn,vf Substitute this into the coupling relationship established in step S3.2.

[0049] ;

[0050] The verification test block D was calculated. 12实 The value.

[0051] Step S4.3: The damage D of the verification test block is calculated. 1-( n,v f) D 2-( n,v f) D 12实 All are coupled with the damage prediction value D of the two corresponding single-damage variable test blocks D1 and D2. 12预 Equal, that is:

[0052] D 12预 ≈D 12实 ≈D1-( n,v f) ≈D 2-( n,v f) .

[0053] Further optimization includes step S4.4 model optimization in step S5, specifically:

[0054] Calculate the coupled damage prediction value D for each pair of single-damage variable test blocks D1 and D2. 12预 Corresponding measured total damage D 12实 The relative error is calculated using the following formula:

[0055] Relative error = | (D 12预 -D 12实 ) / D 12实 |×100%;

[0056] If the relative error of all combinations is ≤5%, the damage model is verified. If the relative error of any combination is >5%, parameter correction is initiated. The least squares method is used to iteratively adjust the coefficients a, b, c, λ1, λ2, and p in D1 and D2. The correction process does not change the definition of D1 and D2 or the structure of the coupling formula, until the relative error of all combinations is ≤5%.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] 1. Dual-factor full-dimensional coupling, precise quantification of synergistic effects: By designing basalt fiber volume content of 0%, 0.5%, 1%, and 1.5%, and sodium sulfate solution concentration gradients of 0%, 5%, 10%, 15%, and 20%, the full-parameter combination damage coupling of sulfate erosion and basalt fiber content is realized. The damage law of concrete under the combined action of the two types of factors can be quantified, which solves the limitation of single-factor analysis in existing technologies.

[0059] 2. The test conditions closely match the actual engineering situation, and the data is highly referential: The 30-day continuous immersion erosion method is fully matched to the actual service environment of concrete in water conservancy projects where it is in long-term contact with sulfate-containing saline water; at the same time, the decline mechanism of concrete tensile strength and elastic modulus under different combinations is observed. The data obtained can directly reflect the performance degradation process of concrete in actual engineering. Compared with the dry-wet cycle accelerated test, the results are more valuable for engineering guidance.

[0060] 3. Synergistic characterization of indicators for more comprehensive damage description: Simultaneous testing of two core mechanical parameters, tensile strength (characterizing load-bearing capacity) and elastic modulus (characterizing stiffness characteristics), combined with the variation law of the two to analyze the concrete damage mechanism, realizing the synergistic characterization of "strength + stiffness", which makes up for the shortcomings of existing technologies that only test strength and cannot fully reflect damage.

[0061] 4. Based on Lemaitre's equivalent strain theory, a damage model is constructed to quantify the change law of concrete performance corresponding to "fiber content - sulfate concentration" with damage variables. This clearly characterizes the influence logic of the two types of factors on the internal damage of concrete, avoiding the problem of vague physical meaning in simple mathematical fitting models.

[0062] 5. Excellent model accuracy and strong engineering applicability: The coupled damage model has a fitting determination coefficient R²≥0.9 and a relative error of ≤5% in the verification stage. It can accurately assess the degree of concrete damage under different fiber dosages and different sulfate concentrations. At the same time, it can directly provide the optimal dosage reference of basalt fiber for water conservancy projects, help improve the sulfate resistance of concrete, and has clear engineering application value. Attached Figure Description

[0063] Figure 1 This is a flowchart of the method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion as described in this invention;

[0064] Figure 2 This is a diagram illustrating the concrete specimen preparation and soaking process of the present invention.

[0065] Figure 3 This is a graph showing the relationship between basalt fiber volume content and concrete mechanical properties according to the present invention.

[0066] Figure 4 This is a graph showing the relationship between sodium sulfate concentration and the mechanical properties of concrete according to the present invention.

[0067] Figure 5 This is a comparison chart of the experimental and fitted values ​​of the damage variable D1 in this invention;

[0068] Figure 6 This is a comparison chart of the experimental and fitted values ​​of the damage variable D2 in this invention;

[0069] Figure 7 This is a comparison chart of experimental and fitted values ​​for the first type of coupling damage in this invention;

[0070] Figure 8 This is a comparison chart of experimental and fitted values ​​for the second type of coupling damage in this invention. Detailed Implementation

[0071] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0072] Example 1:

[0073] like Figure 1 As shown, a method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion is described, with the following specific steps:

[0074] Step S1: Prepare control group C30 plain concrete test blocks and experimental group C30 basalt fiber concrete test blocks, and immerse all test blocks in sulfate solutions of different concentrations for a preset time.

[0075] In this embodiment, the raw materials for the control group test blocks included P·O42.5 cement, crushed stone with a particle size of 20~40mm, and natural river sand with a fineness modulus of 2.5. The control group C30 plain concrete test blocks were designated as test block group A.

[0076] The raw materials for the experimental group specimens included P·O42.5 cement, crushed stone with a particle size of 20-40 mm, natural river sand with a fineness modulus of 2.5, and basalt fibers with a length of 6 mm and a diameter of 11 μm. The C30 basalt fiber reinforced concrete specimens were divided into three groups, designated as specimen group B, specimen group C, and specimen group D, with fiber volume contents of 0.5%, 1%, and 1.5% for the three groups, respectively.

[0077] Each test block group contains 30 test blocks, each measuring 100×100×100mm. All test blocks are numbered, with each block corresponding to a unique number. For each group of test blocks with different numbers, they are immersed in solutions with sulfate concentrations of 0%, 5%, 10%, 15%, and 20%, respectively, for a total immersion and etching time of 30 days. The test block preparation process is as follows: Figure 2 As shown.

[0078] Step S2: Conduct mechanical property tests on the eroded concrete to obtain two mechanical property parameters: tensile strength and elastic modulus.

[0079] In this embodiment, the soaked test blocks were dried at a constant temperature for 24 hours. Then, an RFP-03 intelligent force gauge was used to test the mechanical properties of the four groups of test blocks, measuring their tensile strength and elastic modulus. Under the same influencing factors, the arithmetic mean of the measurements from three parallel test blocks was taken as a valid test result. The test results are shown in Table 1.

[0080] Table 1 Experimental data of test blocks

[0081]

[0082]

[0083] Step S3: Analyze the variation law of the mechanical performance parameters, and construct a concrete damage model under the coupled effect of sulfate attack and basalt fiber content based on Lemaitre's equivalent strain theory. The damage model includes the coupling relationship between sulfate attack damage variables and fiber content damage variables. Specifically, it includes:

[0084] Step S3.1: Mechanical property test results are as follows Figure 3 and Figure 4 As shown. Among them, Figure 3 Figure (a) shows the relationship between the tensile strength of the specimens after soaking in sodium sulfate solutions of different concentrations and the volume content of basalt fibers. Figure 3 (b) shows the relationship between the elastic modulus of the specimens after soaking in sodium sulfate solutions of different concentrations and the volume content of basalt fibers. Figure 4 Figure (a) shows the relationship between the tensile strength of specimens with different basalt fiber volume contents and the concentration of sodium sulfate solution. Figure 4 Figure (b) shows the relationship between the elastic modulus of specimens with different basalt fiber volume contents and the concentration of sodium sulfate solution.

[0085] from Figure 4 It is evident that the mechanical properties of concrete initially increase slightly with increasing sulfate concentration, then decrease sharply. Basalt fibers with volume contents of 0.5% and 1% can effectively inhibit the sharp decrease in tensile strength of concrete caused by excessively high concentrations of sodium sulfate erosion. Their bridging effect can enhance internal cohesion, increase the ultimate tensile threshold of concrete, and prevent the expansion stress generated by erosion products from causing damage to the concrete interior.

[0086] When the basalt fiber content is 1.5%, an agglomeration effect is formed between the fibers. Due to the smooth surface of the agglomerates, the adhesion to the cement matrix is ​​poor, resulting in poor stress transmission in the concrete specimen, irregular pores, reduced overall density, easy generation and accumulation of erosion products, and the resulting expansion stress damages the interior of the concrete, leading to a sharp decline in mechanical properties.

[0087] Based on experimental results and the definition of damage mechanics, a relative elastic modulus is introduced to reflect the damage variable caused by sulfate erosion of concrete. In this embodiment, the elastic modulus E0 of the specimen corresponding to a sulfate concentration of 0% in specimen group A is used as the baseline value, and the elastic modulus E of the specimen corresponding to a sulfate concentration of n is used as the baseline value. n If the measured value is used, then the damage variable D1 caused by sulfate erosion is expressed as:

[0088] ;

[0089] If D1 < 0, it means that the mechanical properties of the concrete specimen are enhanced after soaking in sulfate solution;

[0090] D1=0 ​​indicates that the mechanical properties of the specimen were not damaged after soaking in sulfate solution;

[0091] If D1>0, it means that the mechanical properties of the test block have been damaged after soaking in sulfate solution.

[0092] The increase in basalt fiber content mainly has a beneficial effect on concrete, but excessive increase can also cause some damage. The relative tensile strength is used as the damage variable D2 reflecting the fiber content. In this embodiment, the tensile strength f of the specimen group A with a sulfate concentration of 0% is used as the reference value. t0 Using the reference value, the tensile strength f of the specimen corresponding to a sulfate concentration of 0% in specimen groups B, C, or D is determined. tn If the measured value is used, then the effect variable D2 caused by the fiber content can be expressed as:

[0093]

[0094] If D2 < 0, it means that the mechanical properties of the concrete specimen are enhanced after adding basalt fiber;

[0095] D2=0 indicates that the addition of basalt fiber has no effect on the mechanical properties of the concrete specimen;

[0096] If D2>0, it means that the mechanical properties of the concrete specimen have been damaged after the addition of basalt fiber.

[0097] Step S3.2: Since the changes in the mechanical properties of concrete are affected by two factors, it is necessary to couple them when constructing the total damage variable. Concrete is a composite material with initial damage, and the mechanical properties in the true undamaged state are difficult to measure directly. Therefore, according to Lemaitre's equivalent strain theory, the undamaged state is defined as the baseline state of damage, while the actual state is defined as the first stage of damage. In this embodiment, the constitutive relationship of the specimen corresponding to a sulfate concentration of 0% in group A is as follows:

[0098]

[0099] In the formula: D0 represents the initial damage of the specimen corresponding to a sulfate concentration of 0% in group A, and σ and ε represent the stress and strain of the specimen corresponding to a sulfate concentration of 0% in group A under actual conditions.

[0100] Sulfate erosion damage and fiber doping damage were coupled to construct the total damage variable D. 12预 Constitutive relations:

[0101] ;

[0102] In the formula, D 12预This represents the predicted values ​​of concrete damage variables under the coupling effect of sulfate attack and basalt fibers; when only sulfate attack exists, D2=0, D... 12预 =D1; When only the fiber content has an effect, D1=0, D 12预 =D2; When both exist simultaneously, consider the interaction between the stress generated by fiber bridging and agglomeration effects and the expansion stress of sulfate erosion products.

[0103] Substituting D1 and D2, we get:

[0104] ;

[0105] Step S3.3: Based on the law of change in mechanical properties, it is assumed that the damage variable D1 has a quadratic function relationship with the change in sulfate concentration, and the D2 has a cubic function relationship with the change in fiber content:

[0106]

[0107]

[0108] In the formula: n is the concentration of sulfate solution, a, b, and c are undetermined coefficients; λ1 and λ2 represent fiber characteristic coefficients, V f Indicates the volume content of basalt, %; l f Indicates the length of basalt, in mm; d f Indicates the diameter of basalt, in μm; This is called the basalt characteristic value, and p is used as an adjustment parameter.

[0109] In this embodiment, regression analysis was performed on D1 and D2 using experimental data, and the fitted curve is shown below. Figure 5 , Figure 6 As shown, the results indicate that the SSE and RMSE values ​​of both models approach 0, and R0... 2 The values ​​are 0.9881 and 0.9943 respectively, as shown in Tables 2 and 3, indicating a high degree of fit. The fitted model equations and parameters are as follows:

[0110]

[0111]

[0112] Table 2 Model parameters for damage variable D1

[0113]

[0114] Table 3 Model parameters for damage variable D2

[0115]

[0116] Step S3.4: Couple D1 and D2, and obtain two types of damage coupling models through parameter fitting:

[0117] The first category consists of damage coupling models that vary with basalt fiber volume content when the sulfate concentration is constant, as shown in Table 4, and are detailed below:

[0118]

[0119] Among them, D 12预 _0S、D 12预 _5S、D 12预 _10S、D 12预 _15S、D 12预 _20S represent the damage coupling models when the sulfate concentration is 0%, 5%, 10%, 15%, and 20%, respectively.

[0120] The second category consists of damage coupling models that vary with sulfate concentration when the basalt fiber volume content is fixed, as shown in Table 5, and are detailed below:

[0121]

[0122] Among them, D 12预 _0F、D 12预 0.5F, D 12预 _1F、D 12预 _1.5F represents the damage coupling model when the volume content of basalt fiber is 0%, 0.5%, 1.0%, and 1.5%.

[0123] Table 4 Model parameters for type I coupling damage

[0124]

[0125] Table 5 Model parameters for the second type of coupling damage

[0126]

[0127] Among them, the SSE and RMSE values ​​of the first type of coupling damage both tend to 0, and R 2 All values ​​exceeding 0.9 indicate a good fit, and the model can intuitively reflect the damage pattern. In the second type of coupled damage, excluding the damage variable D... 12 _0.5F of R 2 Except for 0.8282, the SSE and RMSE values ​​of other variables all tend to 0, and R0 2 All values ​​exceeded 0.9. Overall, the coupled damage model effectively reflects the damage patterns of concrete under the influence of both sulfate attack and fiber content variations.

[0128] S4: Step S4.1: Determine the verification object: Determine the test blocks corresponding to the 12 independent combinations of fiber volume content of 0.5%, 1%, and 1.5% and sulfate concentration of 5%, 10%, 15%, and 20% in the test group as verification test blocks. All verification test blocks constitute verification group E, and each combination contains no less than 3 parallel test blocks.

[0129] Step S4.2: Calculate the total measured damage for each combination in verification group E, specifically as follows:

[0130] 1) The elastic modulus E0 of the specimen in specimen group A with a sulfate concentration of 0% is used as the baseline value; the sulfate concentration n and basalt fiber volume content V in experimental group E are used as the baseline value. f The elastic modulus E of the corresponding test block n,vf If the measured value is given, then the damage D of the verification test block is... 1-( n,v f) =1-E n,vf / E0;

[0131] 2) The tensile strength f of the test block corresponding to a sulfate concentration of 0% in test block group A. t0 Using the sulfate concentration n and basalt fiber volume content V in experimental group E as the baseline values, f Corresponding elastic modulus f tn,vf If the measured value is given, then the damage D of the verification test block is... 2-( n,v f) =1-f tn,vf / f t0 ;

[0132] 3) The measured E n,vf f tn,vf Substitute this into the coupling relationship established in step S3.2.

[0133] ;

[0134] The verification test block D was calculated. 12实 The value.

[0135] Step S4.3: The damage D of the verification test block is calculated. 1-( n,v f) D 2-( n,v f) D 12实 All are coupled with the damage prediction value D of the two corresponding single-damage variable test blocks D1 and D2. 12预 Equal, that is:

[0136] D 12预 ≈D 12实 ≈D 1-( n,v f) ≈D 2-(n,v f) .

[0137] In this embodiment, the damage model constructed in step S3 is fitted to the calculated result D. 12预 Damage results of test block group D 12实 Highly matched, the result is as follows Figure 7 and Figure 8 As shown, the damage trends of sodium sulfate erosion and basalt fiber content were comprehensively evaluated. Basalt fiber concrete with 1% content showed the strongest resistance to sodium sulfate erosion, while sulfate erosion with a concentration of 5% or higher would lead to a sharp decline in the mechanical properties of the concrete.

[0138] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion, characterized in that, Includes the following steps: Step S1: Prepare control group C30 plain concrete test blocks and experimental group C30 basalt fiber concrete test blocks, and immerse all test blocks in sulfate solutions of different concentrations for a preset time. Step S2: Dry the concrete test blocks after soaking and erosion, and then conduct mechanical property tests to obtain at least two key mechanical property parameters; Step S3: Analyze the variation law of the mechanical performance parameters, and construct a concrete damage model under the coupled effect of sulfate attack and basalt fiber content based on Lemaitre equivalent strain theory. The damage model includes the coupling relationship between sulfate attack damage variables and fiber content damage variables. Step S4: Repeat the mechanical property test in step S2 to verify and correct the damage model so that the model fitting calculation results and the experimental test damage results meet the preset matching accuracy.

2. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 1, characterized in that, The raw materials for the control group test blocks included P·O42.5 cement, crushed stone with a particle size of 20~40mm, and natural river sand with a fineness modulus of 2.5; The raw materials for the experimental group test blocks included P·O42.5 cement, crushed stone with a particle size of 20~40mm, natural river sand with a fineness modulus of 2.5, and basalt fiber.

3. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 2, characterized in that, In step S1, the control group C30 plain concrete test blocks are designated as test block group A; the experimental group C30 basalt fiber reinforced concrete test blocks are divided into three groups, designated as test block group B, test block group C, and test block group D, respectively, with fiber volume contents of 0.5%, 1%, and 1.5% for the three groups of test blocks, respectively. Each test block group contains multiple test blocks, and all test blocks are numbered, with each test block corresponding to a unique number; For each group of test blocks with different numbers, they were immersed in solutions with sulfate concentrations of 0%, 5%, 10%, 15%, and 20%, respectively, for a period of N days.

4. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 3, characterized in that, In step S2, mechanical property tests are conducted on all test blocks. The values ​​of the elastic modulus and tensile strength of different test blocks are collected. Under the same influencing factors, the arithmetic mean of the values ​​measured by three parallel test blocks is taken as a valid test result.

5. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 4, characterized in that, Step S3 specifically includes: Step S3.1: Define sulfate erosion damage variable D1: Using the elastic modulus E0 of the specimen corresponding to a sulfate concentration of 0% in specimen group A as the baseline value, and the elastic modulus E of the specimen corresponding to a sulfate concentration of n... n If the measured value is true, then: D1 = 1 - E n / E0; If D1 < 0, it means that the mechanical properties of the concrete specimen are enhanced after soaking in sulfate solution; D1=0 ​​indicates that the mechanical properties of the specimen were not damaged after soaking in sulfate solution; If D1>0, it means that the mechanical properties of the test block have been damaged after soaking in sulfate solution; Define the basalt fiber admixture effect variable D2: the tensile strength f of the specimen corresponding to a sulfate concentration of 0% in specimen group A. t0 Using the reference value, the tensile strength f of the specimen corresponding to a sulfate concentration of 0% in specimen groups B, C, or D is determined. tn If the measured value is true, then: D2 = 1 - f tn / f t0 ; If D2 < 0, it means that the mechanical properties of the concrete specimen are enhanced after adding basalt fiber; D2=0 indicates that the addition of basalt fiber has no effect on the mechanical properties of the concrete specimen; If D2>0, it means that the mechanical properties of the concrete specimen have been damaged after the addition of basalt fiber; Step S3.2: Establish the coupling relationship between D1 and D2: Based on Lemaitre's equivalent strain theory, sulfate erosion damage and fiber doping damage are coupled to construct the total damage variable D. 12预 Constitutive relations: ; In the formula, D 12预 This represents the predicted values ​​of concrete damage variables under the coupling effect of sulfate attack and basalt fibers; when only sulfate attack exists, D2=0, D... 12预 =D1; When only the fiber content has an effect, D1=0, D 12预 =D2; Step S3.3: Establish functional relationships: The damage variable D1 is set to have a quadratic function relationship with the sulfate concentration: D1 = an² + bn + c, where n is the sulfate solution concentration and a, b, and c are coefficients to be determined. The damage variable D2 is set to have a cubic function relationship with the basalt fiber content: V f The volume content of basalt fiber, l f Indicates the length of basalt fibers, in mm; d f The diameter of the basalt fiber is expressed in μm. λ1 and λ2 represent the characteristic values ​​of basalt fibers, p is an adjustment parameter, and λ1 and λ2 represent the characteristic value coefficients of basalt fibers. Step S3.4: Model parameter fitting: The sulfate is sodium sulfate. The functional relationship in step S3 is subjected to regression analysis using the test results of step S2 to obtain the fitting parameters. The fitting parameters for D1 satisfy: a = 3.0 × 10 -4 b = -4.0 × 10 -4 c = -2.7 × 10 -3 ; The fitting parameters for D2 satisfy: λ1 = 2.6265 × 10 -6 λ2=-3.2902×10 -9 p = 8.3784 × 10 -3 .

6. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 5, characterized in that, In step S3.4, two types of damage coupling models are obtained through parameter fitting: The first type is a damage coupling model that considers the variation of basalt fiber volume content when the sulfate concentration is constant, as detailed below: ; Among them, D 12预 _0S、D 12预 _5S、D 12预 _10S、D 12预 _15S、D 12预 _20S represent the damage coupling models when the sulfate concentration is 0%, 5%, 10%, 15%, and 20%, respectively; The second category is the damage coupling model that varies with sulfate concentration when the basalt fiber volume content is constant, as detailed below: ; Among them, D 12预 _0F、D 12预 0.5F, D 12预 _1F、D 12预 _1.5F represents the damage coupling model when the volume content of basalt fiber is 0%, 0.5%, 1.0%, and 1.5%.

7. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 6, characterized in that, Step S4 specifically includes: Step S4.1: Determine the verification object: Determine the test blocks corresponding to the 12 independent combinations of fiber volume content of 0.5%, 1%, and 1.5% and sulfate concentration of 5%, 10%, 15%, and 20% in the test group as verification test blocks. All verification test blocks constitute verification group E, and each combination contains no less than 3 parallel test blocks. Step S4.2: Calculate the total measured damage for each combination in verification group E, specifically as follows: 1) The elastic modulus E0 of the specimen in specimen group A with a sulfate concentration of 0% is used as the baseline value; the sulfate concentration n and basalt fiber volume content V in experimental group E are used as the baseline value. f The elastic modulus E of the corresponding test block n,vf If the measured value is given, then the damage D of the verification test block is... 1-( n,v f) =1-E n,vf / E0; 2) The tensile strength f of the test block corresponding to a sulfate concentration of 0% in test block group A. t0 Using the sulfate concentration n and basalt fiber volume content V in experimental group E as the baseline values, f Corresponding elastic modulus f tn,vf If the measured value is given, then the damage D of the verification test block is... 2-( n,v f) =1-f tn,vf / f t0 ; 3) The measured E n,vf f tn,vf Substitute this into the coupling relationship established in step S3.

2. ; The verification test block D was calculated. 12实 The value; Step S4.3: The damage D of the verification test block is calculated. 1-( n,v f) D 2-( n,v f) D 12实 All are coupled with the damage prediction value D of the two corresponding single-damage variable test blocks D1 and D2. 12预 Equal, that is: D 12预 ≈D 12实 ≈D 1-( n,v f) ≈D 2-( n,v f) 。 8. The method for constructing a damage model of basalt fiber-reinforced concrete under sulfate erosion according to claim 7, characterized in that, Step S4 also includes step S4.4 model optimization, specifically: Calculate the coupled damage prediction value D for each pair of single-damage variable test blocks D1 and D2. 12预 Corresponding measured total damage D 12实 The relative error is calculated using the following formula: Relative error = | (D 12预 -D 12实 ) / D 12实 |×100%; If the relative error of all combinations is ≤5%, the damage model is verified. If the relative error of any combination is >5%, parameter correction is initiated. The least squares method is used to iteratively adjust the coefficients a, b, c, λ1, λ2, and p in D1 and D2. The correction process does not change the definition of D1 and D2 or the structure of the coupling formula, until the relative error of all combinations is ≤5%.